Pengaruh Perputaran Modal Kerja, Leverage dan Pertumbuhan Penjualan Terhadap Profitabilas Pada Perusahaan Sektor Perdagangan Besar Yang Terdaftar Di Bursa Efek Indonesia Pada Tahun 2019-2021 - Pinky Silvia Putri; Wikan Budi Utami; Rukmini (Jurnal Ilmiah Keuangan Akuntansi Bisnis (JIKAB), 2023)
The purpose of this observation is to analyze Working Capital Turnover, Leverage and Growth Ratio on Profitability in the big trading companies (wholesale) listed on Indonesia stock exchange 2019 – 2021. This study is uses secondary data with a 40 population of the big trading companies (wholesale) based on Indonesia stock exchange 2019 – 2021. The technique used is descriptive statistical test, classical assumption test. Another trials hypothesis testing which includes multiple linear regression test. The results of the multiple linear regression test showed that the working capital turnover variable had no effect on profitability, while leverage and sales growth had a significant effect on profitability. Moreover, the adjusted R square value of 0.297 means that working capital turnover, leverage and sales growth contribute 29.7% to the value of the trading companies (wholesale) based on the Indonesia Stock Exchange in 2019-2021, while the remaining 71.3% is explained by other variables outside the model studied. Keywords: Profitability, Working Capital Turnover, Leverage, and Growth Ratio